Conventional thyroidectomy vs thyroid thermal ablation on postoperative quality of life and satisfaction for patients with benign thyroid nodules. Issue 1 (January 2021) - Jin, Hao; Lin, Weidong; Lu, Ligong; Cui, Min
Abstract : Objective: The complications and treatment effects of conventional thyroidectomy and thyroid thermal ablation should be compared in order to identify the best intervention for patients with benign thyroid nodules. Methods: Patients (18–50 years old) who had benign thyroid nodules and were eligible for both thyroidectomy and thyroid thermal ablation were randomly allocated (1:1) to either conventional thyroidectomy group or thyroid thermal ablation group. Patients' satisfaction and condition-specific quality of life were measured with the Thyroid-Specific Quality-of-Life Questionnaire Scale (QoL) at the 15th post-randomization month and were set as the co-primary outcome. Results: A total of 450 patients were enrolled and randomized (225 patients in each group). At the 15th month after randomization, more patients in the thyroid thermal ablation group were satisfied with the treatment effects compared to those in the conventional thyroidectomy group. More patients in the thyroid thermal ablation group have a QoL score of 410 (QOL scores ranges from 0 to 410) than patients in conventional thyroidectomy. Eight (4%) of the 209 patients in conventional thyroidectomy group and 6 (3%) of the 208 patients in thyroid thermal ablation group had at least one severe postoperative complication. The time to achieve volume reduction was longer in the thermal ablation group. Conclusion: Thyroid thermal ablation is superior to conventional thyroidectomy in terms of patients satisfaction, post-operative quality of life, and shorter hospital stay but takes longer to achieve BTNs volume reduction. The complication rates between the two groups were similar.